SYNTHESIS OF MAGNETIC NANOPARTICLES OF TiO2-NiFe2O4: CHARACTERIZATION AND PHOTOCATALYTIC ACTIVITY ON DEGRADATION OF RHODAMINE B - Rahmayeni Rahmayeni; Syukri Arief; Yeni Stiadi; Rianda Rizal; Zulhadjri Zulhadjri (Indonesian Journal of Chemistry, 2012)
Magnetic nanoparticles of TiO2-(x)NiFe2O4 with x = 0.01, 0.1, and 0.3have been synthesized by mixture of titanium isopropoxide (TIP) and nitric metal as precursors. The particles were characterized by XRD, SEM-EDX, and VSM. XRD pattern show the peaks at 2q = 25.3°, 38.4° and 47.9° which are referred as anatase phase of TiO2. Meanwhile NiFe2O4 phase was observed clearly for x = 0.3. The present of NiFe2O4 can prevent the transformation of TiO2 from anatase to rutile when the calcination temperature increased. Microstructure analyses by SEM show the homogeneous form and size of particles. The magnetic properties analysis by VSM indicates that TiO2-NiFe2O4 is paramagnetic behavior. TiO2 doped NiFe2O4 has higher photocatalytic activity than TiO2 synthesized for degradation of Rhodamine B in aqueous solution under solar light irradiation.